Pengembangan Daerah Tujuan Wisata: Peran dan Strategi Dinas Pariwisata Kabupaten Aceh Tengah - Yuli Santri Isma (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Tourism development in Aceh Tengah Regency has great potential to become a leading tourist destination, especially with the natural beauty of Danau Laut Tawar and the richness of local culture. The Tourism Office of Aceh Tengah Regency has implemented various strategies, including the empowerment of local communities, infrastructure improvements, and tourism promotion. However, significant challenges remain in the development of this sector, such as the lack of land legality documents, limited supporting facilities, and low creativity in the creative economy products. Based on the research, development focusing on community empowerment through training, improvements in physical and social infrastructure, and strengthening collaboration between the government, private sector, and local communities can enhance tourism appeal and provide positive economic impacts. In the future, community-based and sustainable tourism development will be the key to creating an environmentally friendly and sustainable destination. Through more coordinated strategic efforts, it is expected that the tourism sector in Aceh Tengah can grow rapidly and contribute to regional development.